The use of urine lipoarabinomannan for establishing pulmonary TB in HIV patient: case report and systematic review - Margono, Djiwa; Yulianti Ningtias, Pranudiah; Kusumaningrum, Ardiana; Prasetyo, Dimas Seto (Indonesian Society for Clinical Microbiology (Perhimpunan Dokter Spesialis Mikrobiologi Klinik Indonesia), 2023)
Introduction: Indonesia is still the country that provides the second-largest estimated number of TB cases worldwide. Several patients had TB with HIV-positive. HIV-positive patients with symptoms suggestive of pulmonary tuberculosis often difficult to produce sputum of sufficient quality. Lateral flow lipoarabinomannan examination with urine specimens is expected to be easy, inexpensive, fast, and accurate point-of-care testing. The aim of this research was to assess the sensitivity and specificity of the lateral flow method in detecting lipoarabinomannan (LAM) from urine specimens in HIV-positive patients with suspected pulmonary tuberculosis. Sputum cultures were utilised as a reference standard. Case Description: A 21-year-old male patient came to the clinic complaining of a cough that had not subsided since the previous month. Cough felt throughout the day with a little white phlegm. The patient admitted to having high-risk sexual behavior and had been tested positive for HIV but had not started antiretroviral therapy. The laboratory examination results showed that the leukocyte count was 3600/mm3 and the radiological examination revealed a chest X-ray within normal limits. The patient had been tested for sputum smears with negative results but was still advised to start TB treatment. The patient has not started treatment because he feels that his sputum smear test results are negative. Currently, the patient is not willing to have his sputum checked again. The polyclinic doctor knows the lipoarabinomannan (LAM) examination that uses urine specimens to diagnose TB but does not yet know its effectiveness for this patient. Conclusion: In this case report, the patient was unwilling to do a diagnostic test related to the TB. The systematic review was that the Alere Determine™ TB LAM Ag may not be clinically applicable for diagnosing tuberculosis infection in patients living with HIV at this time. However, Fujifilm SILVAMP TB LAM® could be regarded as a supplementary tool to the established diagnostic protocol for tuberculosis in HIV-positive patients.